The Therapeutic Potential Of Date Palm Pollen For Testicular Disorders Induced By Diabetes In Male Diabetic Rats - Jaiballah, Zainab; Lji, Naji; Younes, Mohamed (Journal of Pure & Applied Sciences, 2023)
Diabetes mellitus (DM) is the main cause of large-scale morbidity and mortality. This syndrome has adverse effects on all physiological systems, including the male reproductive system. It affects a large number of men of reproductive age and causes serious reproductive disorders. This study was aimed to examine the protective effect of date palm pollen (DPP) on diabetes-induced testicular disorders in male rats. Rats were divided into 4 groups. The first group represents the negative control, while the second group is the positive control. In contrast, the following two groups represent the treated groups of DPP suspension with a concentration of 130 mg/kg and 160 mg/kg for 4 weeks. At the end of the experiment, the rats were anesthetized, the epididymis and testis were extracted. The positive control group significantly decreased body weight, sex hormones, and sperm count. However, a significant increase in fasting glucose and the number of abnormal sperm. The histological results confirmed tubular degeneration, Leydig cell atrophy, and tubular dilation. Decrease the basement membrane, the semenforuos epithelium, and tubular diameter, while the diameter of the lumen increased. Treatment with DPP suspension showed a significant decrease in the level of fasting glucose and the number of abnormal sperm. While the number of sperm increased significantly. The results of the histological study confirmed that the Seminiferous Tubules treated with DPP were intact, the germinal epithelium dense, seminiferous tubules did not expand. We concluded that the DPP has an influence on protecting testis from diabetes complication.